ADAPTASI PRANATA KELUARGA PADA PROSES PEMBELAJARAN E-LEARNING DALAM MENGHADAPI DAMPAK PANDEMI COVID-19 - Devi, Nourma Ulva Kumala (Universitas Panca Marga, 2020)
Family has an important role in shaping culture and healthy behavior. The first environment for children and other family members to socialize and learn about clean and healthy living norms is the family environment. From the start of the individual family education, a good community order can be created and a culture and healthy behavior can be instilled earlier. In addition, the family is a place to gather, discuss, share and socialize for all family members. In accordance with the function of the family as a place to socialize and learn, the family acts as an institution capable of providing education and as an